Clinical case of COVID-19 in a patient with Hodgkin's lymphoma - D. A. Malashenko; Zh. B. Ponezheva; A. N. Turapova; E. P. Rodionov; A. A. Ploskireva; M. A. Magomedov; N. G. Burda; I. I. Tsvetaev; T. A. Trubina (Лечащий Врач, 2023)
Background. At present, infection caused by the SARS-CoV-2 virus is one of the most urgent problems of infectious pathology. The total number of cases of a new coronavirus infection in the Russian Federation exceeded 22 million, of which more than 398 thousand cases were fatal.All resources of the healthcare organizations around the world were thrown into the fight against the coronavirus pandemic, which affected the quality of medical care for patients with other diseases. During the pandemic, data have been accumulated on the peculiarities of the course of COVID-19 infection, the clinical manifestations of which are variable: from an asymptomatic course to the development of massive lung damage and acute respiratory distress syndrome. Risk factors for severe COVID-19 are age over 60 years, comorbid background, including immunodeficiency conditions. Oncohematological diseases are associated with the highest risk of death from COVID-19. A particular danger is the development of COVID-19 infection in a time interval of less than 14 days from the course of antitumor therapy. Hodgkin's lymphoma is a localized or disseminated proliferation of cells of the lymphoreticular system, which can affect the lymph nodes, spleen, liver or bone marrow. Due to the progressive insufficiency of cellular and humoral immunity of the underlying pathology, as well as suppressing the immune response of treatment, such patients have a high risk of infection with SARSCoV-2, severe course.Objective. The present article describes a clinical case of COVID-19 with the development of severe respiratory distress syndrome against the background of a critical lesion of the lung tissue in an immunosuppressive patient.Results. The dynamics of the patient's condition against the background of respiratory support is described, and laboratory parameters during treatment are given. Despite the high mortality among patients with oncohematology, in connection with the previous immunosuppressive and toxic therapy, the outcome of the disease in this patient was favorable due to the timely detection of SARS-CoV-2, hospitalization in the hospital, as well as the correct tactics of treating the patient.